Incidence and characteristics of errors detected by a short team briefing in pediatric anesthesia. Issue 10 (31st July 2022) - Keil, Oliver; Brunsmann, Katja; Boethig, Dietmar; Dennhardt, Nils; Eismann, Hendrik; Girke, Stefan; Horke, Alexander; Nickel, Katja; Rigterink, Vanessa; Sümpelmann, Robert; Beck, Christiane E.
Abstract: Background: In our institution, a modified WHO surgical safety checklist was implemented more than ten years ago. In retrospect, we noticed that pediatric anesthesia was underrepresented in our surgical safety checklist modification. Therefore, we added a standardized team briefing (pedSOAP‐M) immediately before induction of anesthesia and hypothesized that the use of this checklist was effective to detect relevant errors with potentially harmful consequences. Aims: The primary aim was to assess the incidence and characteristics of the detected errors, and the secondary aim was to identify factors influencing error detection. Methods: This prospective observational study was performed between November 2020 and October 2021 in five operation rooms at the Children's Hospital of Hannover Medical School, Germany. The subcategories of the pedSOAP‐M checklist were suction, oxygen, airway, pharmaceuticals, and monitoring. Demographic and procedure‐related data and the briefing results were documented anonymously and undated, using a standardized case report form. Results: We enrolled 1030 and analyzed 1025 patients (aged 0–18 years). Relevant errors were detected in 111 (10.8%) cases (suction 2.5%, oxygen 3.0%, airway 0.2%, pharmaceuticals 2.4%, monitoring 3.0%). In the pharmaceuticals subcategory, the most common error was entering a wrong patient weight into the perfusor syringe pumps. Experienced anesthetists detected significantly more errors than less experienced ones. Conclusion: The briefing tool pedSOAP‐M was effective in detecting relevant errors with potentially harmful consequences. The presence of an experienced anesthetist was associated with a higher efficacy of the briefing. Particular attention should be given to entering patient weight into the anesthesia workstation and the perfusor syringe pumps.